A continuous process for biodiesel production in a fixed bed reactor packed with cation-exchange resin as heterogeneous catalyst - Feng, Yaohui; Zhang, Aiqing; Li, Jianxin; He, Benqiao (Bioresource technology, 2011)
Continuous esterification of free fatty acids (FFA) from acidified oil with methanol was carried out with NKC-9 cation-exchange resin in a fixed bed reactor with an internal diameter of 25mm and a height of 450mm to produce biodiesel. The results showed that the FFA conversion increased with increases in methanol/oil mass ratio, reaction temperature and catalyst bed height, whereas decreased with increases in initial water content in feedstock and feed flow rate. The FFA conversion kept over 98.0% during 500h of continuous esterification processes under 2.8:1 methanol to oleic acid mass ratio, 44.0cm catalyst bed height, 0.62ml/min feed flow rate and 65°C reaction temperature, showing a much high conversion and operational stability. Furthermore, the loss of sulfonic acid groups from NKC-9 resin into the production was not found during continuous esterification. In sum, NKC-9 resin shows the potential commercial applications to esterification of FFA.